S53 Studying fibre specific gene expression in COPD using laser capture micro-dissection in human skeletal muscle. (14th November 2013) - Mohan, D; Lewis, A; Patel, MS; Curtis, K; Tanner, R; Kemp, P; Polkey, MI
Abstract : Background: Approximately 30% of patients with Chronic Obstructive Pulmonary Disease (COPD) exhibit peripheral skeletal muscle dysfunction and a shift towards type II glycolytic fibres in the quadriceps compared to healthy controls (Nanatek et al, 2013). Previous work to elucidate the molecular mechanisms underlying these changes has relied on whole biopsy samples and may have missed fibre-specific pathways; thus a method to evaluate fibre specific signalling pathways would be useful. Objective: To describe a novel laser capture micro-dissection (LCM) method to examine fibre-specific signalling in quadriceps biopsies. Methods: First larger Intercostal muscle biopsies were used to validate the methodology since they yielded more RNA. Fibres were classified as type-2 positive or type-2 negative based on immunoreactivity with a type-2 fibre specific anti-myosin Heavy Chain Alexa FLUOR 488 antibody. The type-2 negative fibre population was hence assumed to contain type-1 fibres, which was confirmed by the type-2 negative fibre population exhibiting a higher myhc7/2 mRNA ratio and expressing higher levels of genes associated with type-1 fibres, e.g. TNNT-1 and STARS, and lower levels of genes associated with type-2 fibres, e.g. TGF-B, myostatin, GAPDH and HDAC-4 (n = 2). We then examined OCT-embedded vastus lateralis muscle biopsy specimens. 10micron cryosections underwent fixation with 4% paraformaldehyde before immunostaining. LCM (PALM Microbeam, Zeiss, UK) was used to capture type I and type II fibre populations, before RNA extraction with RNAeasy FFPE kit (Qiagen, USA) and rtPCR to obtain cDNA. Sybr-II qPCR was performed on fibre populations for target genes MHC I, MHC IIa, MHC IIx, HDAC-4 and RPLPO. Results: Preliminary results from three 10micron slices indicate that this technique is feasible to study fibre-specific signalling in COPD. LCM following immunostaining captures distinct fibre populations (Figure 1 ) confirmed by a higher MHC I content in 'type I fibres', with 'type II' fibres containing more MHC IIa, MHC IIx and HDAC-4 as would be expected. Gene expression is normalised against RPLPO. Conclusion: LCM can be used to study fibre specific inflammatory signalling in the skeletal muscle of COPD patients and immunostaining with MHC antibodies is a feasible way to distinguish between fibre types when capturing composite fibre populations.